The Relationship Between Anxiety Levels and Mothers’ Interest in Choosing the MOW Contraceptive Method Among Multiparous Mothers in Sukarame Village, Pacet Subdistrict, Bandung Regency - Liska, Cici; Irma Damayanti, Neng (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Anxiety levels in multiparous mothers can influence the selection of the Method of Female Surgery (MOW) due to psychological and social pressures, such as concerns about the installation process, often reducing their interest in MOW. Several factors that influence interest include cultural factors regarding negative issues from side effects after the surgical process, education, age, knowledge, parity, family and husband support greatly influence interest. Objective: To determine the relationship between anxiety levels and interest in selecting MOW contraceptive methods in multiparous mothers in Sukarame Village, Pacet District. Method: This research used a quantitative method with a cross-sectional research design. The research variables were anxiety level as the independent variable and interest in selecting MOW contraceptive methods in multiparous mothers as the dependent variable. The sampling technique used was purposive sampling with 62 respondents. Data analysis used the chi square test. Result and Discussion: The results showed that mothers who had no anxiety were 29 people (46.8%), mothers with mild anxiety were 9 people (14.5%), mothers with moderate anxiety were 15 people (24.2%), mothers with severe anxiety were 9 people (14.5%). High interest results were 28 people (45.2%), and low interest were 34 people (54.8%). The results showed that there was a significant relationship between anxiety levels and interest in selecting MOW contraceptive methods in multiparous mothers in Sukarame village, Pacet district with a p-value of 0.029. Conclusions: There is a relationship between anxiety levels and interest in contraceptive method selection in multiparous mothers in Sukarame Village, Pacet District.